Optimal expenditure decentralization for sustainable development: evidence from a 52-country panel analysis - Hui Jin; Fu-Sheng Tsai; Jorge Martinez-Vazquez (Financial Innovation)
Abstract In response to the critical need to balance fiscal expenditure governance with sustainable development, this study identifies the optimal level of fiscal expenditure decentralization that enhances sustainable outcomes. The study aims to determine the optimal expenditure decentralization that maximizes sustainable development outcomes across these dimensions. Theoretically, we analyze the impact mechanism of expenditure decentralization on sustainable development and hypothesize that there is an inverted U-shaped relationship between them, along with the possibility of finding an optimal level of expenditure decentralization. We test this hypothesis by measuring sustainable development in the context of a panel data set for 52 countries covering the period 1991–2016 using the National Sustainable Development Index (NSDI). We find strong support for the inverted U-shaped relationship between expenditure decentralization and sustainable development in both the short and long run. Sustainable development is the coordination of economic, social, and environmental development to balance intergenerational welfare and maximize the total welfare of all generations. Excessive and insufficient expenditure decentralization can potentially negatively affect the efficiency of public goods provision and residents’ utility, thereby adversely impacting total welfare and sustainable development. The results are robust to alternative specifications and to IV estimation to correct for potential endogeneity. The expenditure decentralization level most conducive to sustainable development lies between 30.9% and 34.5%. The optimal decentralization range was determined using the Lind–Mehlum method, supporting the main findings of this study. This research thus contributes to the literature by quantifying the complex relationship between fiscal decentralization policies and sustainable development, providing a clear, actionable pathway for policymakers seeking sustainable outcomes.